Measuring Compact Development Potential of an Emerging Urban Area: A Case of Savar (Journal of Engineering Science, 2024)
Compact development is an urban development policy aimed at promoting high density mixed used city to improve city’s environmental condition. Savar is a fast-growing outer urban area of the capital Dhaka, which is growing through rapid urbanization in the recent decade. As enormous population growth causing the capital city to expand beyond city boundary, Rajdhani Unnayan Kartripakkha (RAJUK), the Capital Development Authority of the Government of Bangladesh has identified Savar as one of the five outer urban areas in the Regional Development Plan (RDP) known as Dhaka Structure Plan (2016-2035) for promoting compact development where various activities of the capital city will shift to minimize the congestion of the core city. For successful implementation of this strategy a careful investigation of the existing spatial structure of these areas is essential for guiding future urban development. Therefore, this study aims to evaluate the potential of these proposed urban areas to accommodate their future growth in a compact manner focusing on Savar, an established urban area of the Dhaka Metropolitan Region. For assessing the compact development potential of Savar, this paper analyzed six indicators of two major aspects of urban form, population and land use pattern using Geographical Information System (GIS). The results of this study revealed that the growth pattern of Savar is still not compact and efficient planning mechanism should be devised for its future growth in a sustainable manner.  The findings of this study will help policymakers, planners, architects and development authorities in policymaking, planning and designing a more sustainable and efficient urban area through compact urban development at intra-urban level.Journal of Engineering Science 14(2), 2023, 107-125